2010
DOI: 10.1177/1545968310380685
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral and Unilateral Arm Training Improve Motor Function Through Differing Neuroplastic Mechanisms

Abstract: Background and Purpose This randomized controlled trial tests the efficacy of bilateral arm training with rhythmic auditory cueing (BATRAC) versus dose-matched therapeutic exercises (DMTEs) on upper-extremity (UE) function in stroke survivors and uses functional magnetic resonance imaging (fMRI) to examine effects on cortical reorganization. Methods A total of 111 adults with chronic UE paresis were randomized to 6 weeks (3×/week) of BATRAC or DMTE. Primary end points of UE assessments of Fugl-Meyer UE Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
211
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(220 citation statements)
references
References 59 publications
3
211
1
3
Order By: Relevance
“…Two meta-analyses and more recent trials suggest that there is a small but measurable benefit compared with no intervention, but no consistent evidence of superiority over other task-specific training interventions has been shown. [695][696][697][698][699] Recent trials comparing bilateral training with CIMT or modified CIMT indicate that they may have similar efficacy for individuals with preserved isolated wrist and finger movement. [700][701][702] For individuals with more severe paresis, the potential for recovery of upper extremity function is greatly reduced, particularly later after stroke.…”
Section: Iib Bmentioning
confidence: 99%
“…Two meta-analyses and more recent trials suggest that there is a small but measurable benefit compared with no intervention, but no consistent evidence of superiority over other task-specific training interventions has been shown. [695][696][697][698][699] Recent trials comparing bilateral training with CIMT or modified CIMT indicate that they may have similar efficacy for individuals with preserved isolated wrist and finger movement. [700][701][702] For individuals with more severe paresis, the potential for recovery of upper extremity function is greatly reduced, particularly later after stroke.…”
Section: Iib Bmentioning
confidence: 99%
“…Furthermore, a 15-minute increase in daily upper limb therapy has no beneficial effects. 16 Bilateral priming is a neuromodulatory adjuvant rather than a therapy and is, therefore, distinct from bilateral isokinematic training or bilateral arm training with auditory cueing, 17,18 which have been found to have no additional benefits by a recent Cochrane review. 19 This study has a number of potential limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement was paralleled by a increase in activation of bilateral premotor cortices after as compared to before training (Luft et al 2004). As compared with conventional physiotherapy according to neurodevelopmental principles, bilateral arm training was as effective but showed a different neural response: where conventional physical therapy had no effect on brain activation, bilateral training lead to an increase in bilateral premotor cortex activation (Whitall et al 2011). This indicated that different therapies operate through different mechanisms even if they induce a comparable behavioral response.…”
Section: Studies In Humansmentioning
confidence: 87%
“…Active training is better than passive movement, but also mental imagery of movement has a training effect in combination with active training (Barclay-Goddard et al 2011). Bilateral training is similarly effective as unilateral training when looking at the population mean; individual patients may respond better to one or the other (Whitall et al 2011). It remains unknown which factors predispose a patient to respond to a specific treatment.…”
Section: Elements Of Effective Trainingmentioning
confidence: 99%